Research on tribological properties of oil containing graphene oxide or hexagonal boron nitride - Patrycja Magdalena Nogas; Krzysztof Gocman; Tadeusz Kałdoński (Biuletyn Wojskowej Akademii Technicznej, 2020)
The aim of this publication is to present the results of studies on the SN-650 oil base with various concentrations of graphene oxide (GO), reduced graphene oxide (rGO) produced by the Institute of Electronic Materials Technology in Warsaw and hexagonal boron nitride (h-BN) produced according to the technology developed at the Military University of Technology. The first part of the publication presents basic information about graphene oxide and the possibilities of its use, in particular in the field of tribology. The second part of the publication presents the results of tests of lubricity properties of the samples with the addition of 0.05%, 0.1%, 0.5%, 1% and 2% of graphene oxide, reduced graphene oxide or hexagonal boron nitride. The measurements were carried out using the UNMT universal nano/microtester tester and the T-02 four-ball device, at the Department of Tribology, Surface Engineering and Logistics of Service Fluids, which is a part of the Institute of Mechanical Vehicles and Transport of the Mechanical Faculty of the Military University of Technology. The obtained results have demonstrated the beneficial effect of introducing additions in the form of graphene oxide or hexagonal boron nitride onto the tribological properties of the oil base. Keywords: graphene, hexagonal boron nitride, graphene oxide, oil base